If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 33 = 4x + 3 Reorder the terms: 33 + 10x = 4x + 3 Reorder the terms: 33 + 10x = 3 + 4x Solving 33 + 10x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 33 + 10x + -4x = 3 + 4x + -4x Combine like terms: 10x + -4x = 6x 33 + 6x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 33 + 6x = 3 + 0 33 + 6x = 3 Add '-33' to each side of the equation. 33 + -33 + 6x = 3 + -33 Combine like terms: 33 + -33 = 0 0 + 6x = 3 + -33 6x = 3 + -33 Combine like terms: 3 + -33 = -30 6x = -30 Divide each side by '6'. x = -5 Simplifying x = -5
| 14+2*-3=0 | | 14+2*21=0 | | 12+8d=60 | | 18w^2y^4-15w^3y^3+9w^4y^2/3w^2y | | 3n+2(n-4)=n+15 | | -13m+21=-9m-7 | | y=3x+(2) | | 9x+30=7(x-2) | | 5x-10=2(x-20) | | 325=24t | | x/6-7=3 | | (3y/5x)(4x^4y^-2/2x^-3y^8)^3 | | 10x+25y=28 | | 2(n+1)=4(n-1) | | -w-12=-3w-22 | | -(x+1)=-2(x+10) | | 3(n-5)=2(n+2) | | 14/9x15/52x8/35 | | -1/100x+60 | | 14/9x15/52x88/35 | | 3x+23=12x+58 | | 4x-4=2x+9 | | (3x-1)/3=(2x+3)/4 | | 2(x+3)=x-1 | | 4.2z=4(.6z-1.2) | | -34+13x=-13x-34 | | -2/5x=1/5 | | 3y=-2x+12 | | 37=-2x+12 | | -8-(-21)= | | 2/3(4x-1)=3/4(2x-4) | | 8n-14=11n-5 |